Analisis Kesesuaian Biaya Riil Terhadap Tarif INA-CBGS Pada Pengobatan Stroke Non Hemoragik Pasien JKN Rawat Inap RSUD Dr. Soehadi Prijonegoro Sragen Tahun 2015 - Ari Dwidayati; Tri Murti Andayani; Chairun Wiedyaningsih (Jurnal Farmasi Indonesia, 2016)
Stroke is one of the degenerative diseases and is also the number one cause of death in Indonesia. Enforcement INA-CBGs (Indonesia Case Based Groups) on the financing of the hospital for stroke patients in need of treatment planning and cost analysis for a costly stroke so that the hospital can make cost savings and is expected to be a solution in controlling health care costs. The purpose of this study was to determine treatment pattern of non-hemorrhagic stroke, correlation between real cost to INA-CBG's cost, and factors affecting the real cost. This study was an observational research, the data was taken retrospectively from the document of national health insurance claim in January-June 2015 period. The descriptive analysis is used for patient characteristic and real cost, the data analysis was conducted using one sample t-test to compare the real cost and INA-CBG’s tariff, correlational test to find out the factors affecting the real cost. The results showned that treatment pattern were citicoline (35,31 %), clopidogrel (26,02 %), amlodipin (7,06 %), simvastatin (5,20 %). Analysis using one sample t-test obtained severity I treatment class 3 Rp. 1.066.143,-, severity II treatment class 3 Rp. 766.848,-, dan severity III treatment class 3 Rp. 931.119,-. Factors that affect were secondary diagnosis, severity, treatment class and LOS.